Desenvolvimento de compósitos de polipropileno (PP) com sabugo de milho (SM) proveniente de resíduos agrícolas - Ramos, Rógerson Rodrigues Freire (2013)
Polymer composites reinforced with agricultural lignocellulosic wastes have been widely studied over the years and increasingly realize the value of its use as an alternative to partial substitution of polymeric materials. Furthermore, the use of lignocellulosic materials in composite adds value to this type of waste which has been used mostly in the feeding of animals and/or fertilization of soils. In this work, corn cob (SM) was used as an alternative particulate filler to polypropylene (PP). PP/SM composites were extruded, injection molded and characterized by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), tensile, flexural and impact tests, and morphological analysis was performed by scanning electron microscopy (SEM). Composites with 5, 10, 20 and 30 wt.% corncob were prepared in order to evaluate the effect of filler content on composite properties. TGA analyses showed that thermal stability of the composites is not significantly affected by addition of corncob. DSC analyses showed that PP crystallinity increased with the presence of corn cob particles, however its transition temperatures did not change significantly. SEM photomicrographs of the composites indicated poor filler/matrix adhesion without evidence of effective stress transfer between the phases. Mechanical tests showed satisfactory results with a slight reduction in mechanical strength of the composites with up to 20 % corncob and decreases for higher filler content. This shows that corncob (a renewable, biodegradable and inexpensive material) can be used to partly replace PP (a non-biodegradable thermoplastic polymer derived from nonrenewable fossil source).